PF-28 Worms Infestation on Stray Cats in Central Bogor - Tetty Barunawati Siagian; Risa Tiuria (Hemera Zoa, 2018)
Stray cats are cats that roam freely in the environment around human beings. Central Bogor is one of the administrative region that is located right at the downtown of Bogor. This region consists of diversity of places such as markets, terminals, campus, schools, housing areas, and many more. The human population in Central Bogor are much more compared to other regions. The diversity of places and dense residential population are one of the factors that increases the cat population in Central Bogor due to the characteristics of the cats that breed and adapt to the environment easily. Stray cats are usually close to human beings, without realizing that their presence has the potential to cause health problems to the society. The outspread of zoonotic parasitic worms is one of the problem caused by stray cats. Research about infestion of zoonotic parasitic worms in Indonesia is still rare compared to pet cats [1,2,3]. Specific research about worm infestation had been done in Central Bogor on pet cats [4] but has never done any on stray cats. The objective of this research is to determine the presence of worm infestations on stray cats in the Central Bogor region.